Cetuximab and Irinotecan With or Without Bevacizumab in Refractory Metastatic Colorectal Cancer: BOND-3, an ACCRU Network Randomized Clinical Trial. (26th February 2022) - Lipsyc-Sharf, Marla; Ou, Fang-Shu; Yurgelun, Matthew B; Rubinson, Douglas A; Schrag, Deborah; Dakhil, Shaker R; Stella, Philip J; Weckstein, Douglas J; Wender, Donald B; Faggen, Meredith; Zemla, Tyler J; Heying, Erica N; et al.
Abstract: Background: Combination irinotecan and cetuximab is approved for irinotecan-refractory metastatic colorectal cancer (mCRC). It is unknown if adding bevacizumab improves outcomes. Patients and Methods: In this multicenter, randomized, double-blind, placebo-controlled phase II trial, patients with irinotecan-refractory RAS- wildtype mCRC and no prior anti-EGFR therapy were randomized to cetuximab 500 mg/m 2, bevacizumab 5 mg/kg, and irinotecan 180 mg/m 2 (or previously tolerated dose) (CBI) versus cetuximab, irinotecan, and placebo (CI) every 2 weeks until disease progression or intolerable toxicity. The primary endpoint was progression-free survival (PFS). Secondary endpoints included overall survival (OS), objective response rate (ORR), and adverse events (AEs). Results: The study closed early after the accrual of 36 out of a planned 120 patients due to changes in funding. Nineteen patients were randomized to CBI and 17 to CI. Baseline characteristics were similar between arms. Median PFS was 9.7 versus 5.5 months for CBI and CI, respectively (1-sided log-rank P = .38; adjusted hazard ratio [HR] = 0.64; 95% confidence interval [CI], 0.25-1.66). Median OS was 19.7 versus 10.2 months for CBI and CI (1-sided log-rank P = .02; adjusted HR = 0.41; 95% CI, 0.15-1.09). ORR was 36.8% for CBI versus 11.8% for CI ( P = .13). Grade 3 or higher AEs occurred in 47% of patients receiving CBI versus 35% for CI ( P = .46). Conclusion: In this prematurely discontinued trial, there was no significant difference in the primary endpoint of PFS between CBI and CI. There was a statistically significant improvement in OS in favor of CBI compared with CI. Further investigation of CBI for the treatment of irinotecan-refractory mCRC is warranted. Clinical Trial Registration: NCT02292758 Abstract : Colorectal cancer is the second most common cause of cancer death in the United States. This article reports results of the BOND-3 trial, which investigated the efficacy and safety of irinotecan and cetuximab with or without bevacizumab in irinotecan-refractory metastatic colorectal cancer.